The Italian National Discourse and the Greek Revolution: Politics, Literature, Art, 1821–1847 - D'Alessandri, Antonio (The Historical Review/La Revue Historique, 2022)
The article investigates the relations between the Italian national discourse during the Risorgimento and the Greek Revolution, from its outbreak to the eve of the European revolutions of 1848. It proposes some general remarks in an attempt to suggest possible points of interpretation of this relation in light of recent historiography. During the period in question, a specific public discourse about Italian national identity was developed in order to create a community of individuals. Within this debate, it is possible to find many references to the Greek experience: from the enthusiasm of the 1820s to the more thoughtful meditations in the two following decades. Political thinkers, writers and artists were deeply impressed by the Greek events. So they used them to find suggestions, examples and possibly models to shape Italian national identity and to prepare the future national revolution.